Occupational Therapy Utilization in Veterans With Dementia: A Retrospective Review of Root Cause Analyses of Falls Leading to Adverse Events. Issue 2 (7th March 2022) - Rhodus, Elizabeth K.; Lancaster, Elizabeth A.; Hunter, Elizabeth G.; Nudell, Tina; Humphrey, Casey; Duke, Mary; Harris, Andrew M.
Abstract : Introduction: Falls in persons with dementia are associated with increased mortality. Occupational therapy (OT) is a rehabilitation discipline, which has, among its goals, the promotion of safety and fall prevention in older adults and those with dementia. The purpose of this study was to evaluate root cause analysis (RCA) data to identify causes of falls with adverse events in patients with dementia who were referred to or receiving OT services within the Veterans Health Administration (VHA). Methods: This study used retrospective review of RCAs within the National Center for Patient Safety database for the VHA. The RCA database was searched using these terms: falls with adverse events, dementia, and OT. Descriptive statistical analysis of demographic information, location, occurrence of orthopedic fracture, and mortality was used. All root causes were qualitatively categorized using thematic analysis of determined causes. Results: Eighty RCAs were included in analysis. Mean age of veterans included was 80 years; 96% were male; 76% resulted in hip fracture; and 20% died as a result of the fall. Occupational therapy evaluations occurred within 7 days of admission to VHA and falls most frequently occurred within 4 days of OT evaluation. Most common causes included inappropriate or lack of equipment (21%), need for falls/rehabilitation assessment (20%), compliance/training to fall protocol of all staff (19%), and behavior/medical status (17%). Conclusions: Earlier identification for OT evaluation need may improve access to services, and use of proper equipment to decrease frequency of falls may improve patient safety for older adults with dementia.